Awareness of age-related change is associated with attitudes toward technology and technology skills among older adults - Schlomann, Anna; Memmer, Nicole; Wahl, Hans-Werner (Frontiers in Psychology, 2022)
Despite much research in the context of aging and technology, the role of Views on Aging (VoA) for differences in technology use and attitudes among older adults has rarely been studied so far. This study focuses on the associations between a multidimensional measure of VoA and technology use, technology skills, and attitudes towards technology in a sample of older adults (n = 369, age range: 65-93 years, 48.2% male). We apply the concept of Awareness of age-related change (AARC) as defined by Diehl and Wahl (2010) to examine the role of positive (AARC-Gains) and negative (AARC-Losses) self-perceptions of aging. Bivariate and multivariate regression analyses were conducted. The results showed positive associations of AARC-Gains with technology skills and technology attitudes. For AARC-Losses, we identified negative associations with technology skills, technology attitudes as well as general technology use. In contrast, associations between subjective age (SA) and all technology-related measures were non-significant. The results stress the importance to consider multidimensional measures of VoA to gain a better understanding of the associations between an individuals’ experiencing of own aging processes and technology adoption. More research is needed to determine the stability of these findings in other samples and for other kinds of technology use and attitudes.